Pengaruh Mutasi Terhadap Semangat Kerja Pegawai Negeri Sipil Di Kantor Regional X Badan Kepegawaian Negara (BKN) Denpasar: Pengaruh Mutasi Terhadap Semangat Kerja Pegawai Negeri Sipil Di Kantor Regional X Badan Kepegawaian Negara (BKN) Denpasar - I Made Surendra; Kadek Mahadewi (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2023)
The Role in the Sustainable Decision Making Process (Case Study at Regional Office X BKN Denpasar) aims to understand more deeply about how the application of management science to sustainable decision making in a company with the scope of human resource management, mutation process, mutation of work spirit as a limitation in implementation writing. This writing is qualitative with a phenomenological approach. The method of data collection is by conducting in-depth interviews, observation and documentation in the process of collecting data with resource persons. The location chosen in the implementation of this writing is at the Regional Office X BKN Denpasar, Bali. From the writing carried out, the results of this paper indicate that in the process of mutation affecting work morale, management knowledge at Regional Office X BKN Denpasar has a role in the decision-making process that is applied in the operational implementation of Regional Office X BKN Denpasar.